2015
DOI: 10.7226/jtfm.21.3.138
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Solubilizing and Antifungal Activity of Root Endophyte Isolated from Shorea leprosula Miq. And Shoreal selanica (DC) Blume.

Abstract: Fungal endophytes are fungi that lives within plant tissues without causing apparent disease. It is also suggested that these fungi have ability to enhance plant growth and plant resistancy against pest and disease. This research is a preliminary study about root fungal endophytes in dipterocarp since there are lack research concerning about this study focus. We examined root fungal endophyte isolated from seedling of Shorea leprosula and Shorea selanica taken from Dramaga Experimental Forest, Bogor. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The use of T. spirale as biological control agent is uncommon and few reports on its biological characterization are available in the literature. Hakim et al (2015) proved a high antifungal index against Fusarium, endophytic behavior and phosphate solubilizing effect of a T. spirale strain from Indonesia but in in vitro conditions. Conversely to the results, T. spirale had low effect controlling F. oxisporum in eggplants under fields conditions comparted to T. hamatum and T. virens (Abdel-Monaim et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…The use of T. spirale as biological control agent is uncommon and few reports on its biological characterization are available in the literature. Hakim et al (2015) proved a high antifungal index against Fusarium, endophytic behavior and phosphate solubilizing effect of a T. spirale strain from Indonesia but in in vitro conditions. Conversely to the results, T. spirale had low effect controlling F. oxisporum in eggplants under fields conditions comparted to T. hamatum and T. virens (Abdel-Monaim et al 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Many fungi identified as endophytic fungi, including Penicillium citrinum. During this research, P. citrinum show the ability to improve the growth of the plant [13]. P. citrinum produced hormone Indole Acetic Acid (IAA), extracellu lar en zy mes, and au xin which can increase the growth of the inoculated plants [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies had also proven that endophytic fungi could solubilize phosphate. Hakim et al (2012) reported that the endophytic fungus Trichoderma spirale isolated from roots could solubilize phosphate in vitro. Priyadharsini and Muthukumar (2017) also reported that the endophytic fungus Curvularia geniculate from the roots of Parthenium hysterophorus could increase plant growth through phosphate solubilization.…”
Section: Discussionmentioning
confidence: 99%